Morphological process found in Fore language in Papua New Guinea - Fatkhiyati, Nurrahma (Lililacs Journal, 2023)
This study is aimed at finding out what morphological processes and morphological rules represented in Fore Language in Papua New Guinea. The data were morphophonemic and taken from “Laboratory Manual for Morphology and Syntax” Seventh Edition written by Merrified et.al., and published in 2003 about Fore Language of Papua New Guinea. The data consist of pronoun markers including first singular (1s), second singular (2s), third singular (3s), and first plural (1p). The Item-and-Process was used to analyze the morphophonemic data. The researcher found that to construct the person markers in Fore Language, the underlying form of the words should be substituted, inserted, or deleted after attached to the underlying form of the suffix. The rests of the findings will be discussed further. Keywords: morphological process; fore language; person marker; morphophonemic; item-and-process